Botanical characteristics, and pharmacological properties of Alangium salviifolium (L.f.) Wang.: A review - Dang, Thị Lệ Thủy; Ly, Hồng Hương Hạ; Nguyen, Thế Nhựt; Nguyen, Thị Hồng Yến; Vo, Khôi Nguyên; Vo, Thị Ngọc Điệp; Le, Trần Thanh Nguyên; Vo, Hiền Vinh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
Alangium salviifolium (L.f.) Wang. (Alangiaceae family) is a valuable medicinal herb of Vietnam, but this herb isn't ettended. To contribute a premise for future studies, the authors have reviewed documents about Alangium salviifolium (L.f.) Wang., such as botanical, chemical components (alkaloids, flavonoids, streroids, terpenoids, tannins, and polyphenols), biology activities (antibacterial, antifungal, antioxidant, anti-inflammatory, analgesic, anti-cancer, cytotoxic, anti-peptic ulcer, hepatoprotective, hypoglycemic, diuretic...). This review contributes to the identification and orientation for future studies on medicinal plant of Alangium salviifolium (L.f.) Wang..